Enhancing Womenpreneurs' Digital Marketing Skills in Purutrejo Village, Purworejo District, Pasuruan - Wiwin Ainis Rohtih; Shidqi Saifuddin Hamzah; Lailatul Sakdiyah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Assistance in utilizing digital marketing for womenpreneurs in the Purutrejo Village is a strategy for female entrepreneurs to expand their market reach and enhance their product sales. This support takes place in the Purutrejo Village using the participatory action research (PAR) method, involving active participation of all stakeholders in planning, implementing and evaluating actions or changes within their bussiness environment. The outcome of this assistance is the acquisition of knowledge and skills necessary for womenpreneurs to confront the challenges and opportunities presented by the dynamic digital market. the mentored womenpreneurs also share their outcome and learning with the PKK and KRPL communities as well as other mothers, through discussions, thereby facilitating the exchange of knowledge and inspiration among womenpreneurs.